Melt-processing, moisture-resistance and strength retention properties of supercritical CO2-processed thermoplastic starch resins - X. L. Peng; M. C. Kuo; C. Y. Huang; W. Wei; D. W. Wang; L. S. Sun; J. Runt; J. T. Yeh (eXPRESS Polymer Letters, 2018)
This paper represents the first report of thermoplastic starch (scCO2TPS) and glutaraldehyde (GA) modified TPS resins (scCO2TPS100GAx), gelatinized and/or modified with the aid of supercritical carbon dioxide (scCO2). The melt flow rate, initial and retention values of tensile strength (σf) of TPS and GA-modified TPS prepared using scCO2 fluid were considerably higher than those of TPS and TPS100GAx materials prepared in the conventional way. After conditioning at 20 °C/50% RH for 56 days, the σf of properly prepared scCO2TPS100GA0.1 still remained at 17.5 MPa, which is around 3.5 times of that of the corresponding conditioned TPS100GA0.1. The moisture contents of conditioned scCO2TPS and scCO2TPS100GAx were considerably lower than those of the corresponding TPS and TPS100GAx aged for the same amounts of time. Conditioned scCO2TPS andscCO2TPS100GAx exhibited only Vh-type crystals with melting temperatures ~20°C lower than those of corresponding conditioned TPS and TPS100GAx. In comparison to TPS and TPS100GAx, more dissociated amylopectin chains with loosely hydrogen-bonded –OH groups and significantly less retrogradation was found for conditioned scCO2TPS and scCO2TPS100GAx.